Examination of newspaper coverage of Hate Crimes: A moral panic perspective - Colomb, Wendy (American journal of criminal justice, 2004)
The role of the media in the construction of social problems is well documented in the social science literature. In some cases, the process of constructing social problems creates a moral panic. In this paper, we contend that a moral panic occurred in the late 1990s regarding hate crimes because of the disproportionate amount of media attention given to the issue. From this panic grew a movement to enact the Hate Crimes Prevention Act of 1999. We quantify Goode and Ben-Yehuda’s (1999) indicators of a moral panic by triangulating sample data, official statistics, and editorials/opinion polls. Results suggest that a moral panic over hate crimes occurred in America during 1998 and 1999.